Morphological Characterization of Matoa the “Permata Papua” Fruit (Pometia pinnata) in Central Java - Endang Yuniastuti; ML Samodra; Muji Rahayu; Iswahyudi Iswahyudi (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2024)
This research aims to obtain morphological character of Matoa (Pometia pinnata JR Forst & G Forst) plant. This research had been conducted from April to October 2021, in 5 Regency (Karanganyar, Klaten, Pati, Sukoharjo, and Surakarta) Central Java. The morphological characther based on direct observation through primary and secondary data recording, and documenting parts of an adult matoa plant with purposive random sampling. Data of morphological characterization of matoa was analyzed using descriptive analysis method with assistance of Ntsys v2.02i program. The results showed a morphological diversity of matoa plant accessions. Fifty (50) matoa accessions exhibit morphological diversity in plant height, canopy diameter, stem circumference, branching type, leaf colour, number of leaflets, compound leaf length, compound leaf petiole length, leaflet width, fruit density, fruit length, fruit weight, seed weight, and fruit skin colour.